Fluorescent test accurately predicts leak of ischemic colon anastomosis in rats - Moschetti,Laura (2017)
Abstract Purpose: To investigate if fluorescein fluorescent test can predict dehiscence in a model of ischemic colonic anastomosis in rats. Methods: This experimental controlled trial randomly assigned 55 rats to four groups. Anastomoses were performed in non-ischemic colon segments (control group) and in ischemic colon segments measuring 1, 2 or 3 cm long (groups 1, 2 and 3, respectively). Fluorescein was injected and the tissues were examined under ultraviolet light. Seven days later, a second-look surgery was performed to check for the presence or absence of anastomosis dehiscence. Results: Twenty-four rats presented anastomotic dehiscence during the second-look surgery. Reticular and nonfluorescent patterns were significantly associated with the occurrence of anastomotic dehiscence. Fluorescein fluorescence had a sensitivity of 95.8%, specificity of 89.2%, positive predictive value of 88.4%, negative predictive value of 96.2%, and accuracy of 92.3% to predict anastomotic dehiscence. Conclusion: Fluorescein fluorescent test can accurately predict leak in a model of ischemic colonic anastomosis in rats.